PREVALENCE OF DEPRESSION OR ANXIETY DURING ANTEPARTUM HOSPITALIZATIONS FOR OBSTETRIC COMPLICATIONS : A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Women with pregnancy problems are more likely to develop perinatal mood disorders or relapse into underlying mood disorders. Objective: This study aimed to look at the prevalence of prenatal depression and anxiety in women admitted to an antepartum ward for obstetric problems. Methods: We searched Pubmed, Embase, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, and ClinicalTrials.gov for English-language papers published between establishing the database in July 2023. The cross-sectional, cohort, case-control, quasi-experimental, and randomized-controlled designs used in the selected studies were all related to the research goal. Results: We discovered 8.799 papers and reviewed 7.918, included in the primary outcome systematic review. Using a 14-question checklist is used to assess the quality of each study. Depression was 34% (95% CI 27-41%), while anxiety was 29% (95% CI 16-43%). Significant clinical and methodologic heterogeneity between trials was expected, and it persisted even after planned a priori subgroup analysis and meta-regression. Nonetheless, the effect direction was constant across trials. There was no evidence of publication bias. Conclusion: According to the current systematic review, one in every three pregnant women hospitalized for obstetric difficulties has clinical depression or anxiety symptoms, double the reported prevalence of prenatal depression or anxiety in the general obstetric population.